Análise de marcadores cromossômicos em Rineloricaria (Siluriformes: Loricariidae) com ênfase na diversidade cariotípica - (:unkn) unknown (UNIVERSIDADE ESTADUAL DE PONTA GROSSA, 2017)
The Loricariidae family is the largest in the Siluriformes order, being comprised of eight subfamilies. One of these, the Loricariinae subfamily, shows great diversity in respect to the number of chromosomes and karyotype formula, varying in the diploid number (2n) from 36 to 74 chromosomes. This diverse range originated mainly from Robertsonian(Rb) rearrangements. Rineloricaria is the largest genre in the Loricariinae subfamily, its species ranging from 2n = 36 to 70 chromosomes. In spite of this, little is known about which kinds of repetitive DNA gave rise to the events of chromosome fusion or fission. Previous studies have revealed the presence of multiple 5S rDNA sites in specimens of Rineloricaria from the Paraná River Basin, associated to the Robertsonian fission/fusion events. The aim of this work was the molecular characterization of the fragile sites associated to the 5S rDNA, besides localizing in situ marker chromosomes in Rineloricaria latirostris from the Das Pedras River and R. latirostris from the Piumhi River (first described in this work), seeking to understand the 2n diversification in this group. Rineloricaria latirostris from the Pedras River exhibited 2n = 46 chromosomes, while those from the Piumhi River presented 2n = 48 chromosomes, and both had a fundamental number (FN) of 60. Fluorescence in situ hybridization (FISH) assays in R. latirostris from the Piumhi River revealed 2 chromosome pairs with 5S rDNA sites, pair 7 with 18S rDNA, and only terminal staining when subjected to a telomeric probe (TTAGGGn). The population of the Pedras river exhibited 5 pairs with 5S rDNA sites, the metacentric (m) pair 2 marked with 18S rDNA, TTAGGGn markers in the terminal regions of the chromosomes, and the presence of interstitial telomeric sites (ITS) in pairs m 1 and m 3. The latter, in synteny with 5S rDNA, is indicative of Robertsonian fusion events. The isolation, cloning and sequencing of the 5S rDNA revealed clones with high sequence identity to 5S rDNA from other species, in addition to the necessary regions for recognition and transcription by RNA polymerase III. One clone of ~700 bp exhibited a degenerated fragment of hAT transposon in its sequence. It was named degenerated 5S rDNA. The fluorescence in situ hybridization assay highlighted chromosomes with co-localized staining for 5S rDNA/hAT, 5S rDNA/degenerated 5S rDNA, and 5S rDNA/ITS (m 3 pair) in R. latirostris from das Pedras River. In R. latirostris from Piumhi River, there was no detection of degenerated 5S rDNA sites. These results allow us to infer the role of the hAT transposon in the dispersion of 5S rDNA sites in the population, since some studies have indicated a relation between 5S rDNA dispersion and transposons in fish. In conclusion, data obtained by this study indicate a possible association between the hAT and the dispersion of 5S rDNA sites and Robertsonian events in the studied population of R. latirostris. The presence of the 5S rDNA/degenerated 5S rDNA/ITS generates hotspots for chromosomal breakage, contributing to the large karyotype diversity found in Loricariidae.
Keywords: DNAs repetitivos; elementos transponíveis; rearranjos cromossômicos; repetitive DNA; transposable elements; chromosomal rearrangement; CNPQ::CIENCIAS BIOLOGICAS::BIOQUIMICA::BIOLOGIA MOLECULAR